Oral health status in children with familial Mediterranean fever - Esmeray, Pelin; Keçeli, Tülin İleri and Tekçiçek, Meryem and Batu, Ezgi Deniz and Arıcı, Zehra Serap and Ünlü, Hande Konşuk and Özen, Seza and Bilginer, Yelda (The Turkish Journal of Pediatrics, 2021)
Background. Familial Mediterranean fever (FMF) is the most common hereditary autoinflammatory disease. We aimed to investigate the oral health status and oral hygiene habits in children with FMF. Methods. In this cross-sectional study, 199 children with FMF, aged between 3-18 years, were included. Demographic findings and oral hygiene habits of children were questioned by face-to-face interview. Oral health status of patients was evaluated using decay-missing-filled index [DMFT (decay-missing-filled teeth), DMFS (decay-missing-filled teeth) for permanent; dmft, dmfs for primary teeth], the International Caries Detection and Assessment System (ICDAS-II) index, PUFA / pufa index [the presence of severely decayed teeth with visible pulpal involvement (P/p), ulceration caused by dislocated tooth fragments (U/u), fistula (F/f) and abscess (A/a)], gingival (GI) and plaque index (PI). In addition to these, occlusion, oral soft and hard tissues were examined. Results. One-hundred-nine (54.8%) of children had at least one decayed permanent tooth and 81.2% of children had at least one decayed primary tooth. The mean DMFT was 1.91±2.45, DMFS was 3.1±4.49, dmft was 3.95±3.54, dmfs was 8.62±8.88, PI was 1.17±0.44, GI was 0.85±0.39. Aphthous mouth ulcer occurred in 19 (9.5%) patients. Recurrent aphthous mouth ulcers were more frequent among patients with one exon-ten and one exon-two mutations than patients with one exon-10 mutation, two exon-ten mutations, or two exon-2 mutations (61.1% vs. 47.9%, 26.1%, 20%, respectively p < 0.001). Tooth decay was more frequent among patients who had attacks in the last six months than those who did not have any attacks during the last six months (97.4% vs. 87.7%, p=0.017). Conclusion. Dental caries and periodontal disease, which are public health problems, were seen at a high percentage of children with FMF in our study.